2022
DOI: 10.1097/qad.0000000000003226
|View full text |Cite
|
Sign up to set email alerts
|

Evolving patterns of antiretroviral drug interactions in people with HIV in British Columbia, Canada

Abstract: Objectives: To characterize the annual prevalence of antiretroviral/nonantiretroviral drug interactions in relation to antiretroviral therapy (ART)-prescribing patterns, and to describe drug interaction-related ART changes.Design/methods: This cohort study included ART-treated adults in British Columbia, Canada between 01 January 2010 and 31 December 2016. Medication dispensing records were abstracted from a population-based, linked administrative-health dataset and used to identify antiretroviral-comedication… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The authors found that numbers of both amber and red DDIs fell over the years studied, an effect they attributed to the move away from boosted protease inhibitor regimens to unboosted integrase inhibitors. 24 This single-center evaluation provides granular evidence that uptake of modern, integrase-containing regimens is associated with a reduction in clinically significant DDIs, whereas studies like ours, while offering broader global representation, are unavoidably heterogenous with less ability to examine the isolated effect of integrase inhibitor use.…”
Section: 4mentioning
confidence: 81%
“…The authors found that numbers of both amber and red DDIs fell over the years studied, an effect they attributed to the move away from boosted protease inhibitor regimens to unboosted integrase inhibitors. 24 This single-center evaluation provides granular evidence that uptake of modern, integrase-containing regimens is associated with a reduction in clinically significant DDIs, whereas studies like ours, while offering broader global representation, are unavoidably heterogenous with less ability to examine the isolated effect of integrase inhibitor use.…”
Section: 4mentioning
confidence: 81%
“…32,[35][36][37][38][39][40] After the discontinuation of the offending corticosteroid, secondary adrenal insufficiency marked by low levels of adrenocorticotropic hormone (ACTH) can then occur. 31,38,39,[41][42][43][44][45] In a retrospective chart review, 11% of PLHIV who were taking a protease inhibitor when they received a steroid injection developed an abnormality of adrenal function. 46 Tertiary adrenal insufficiency results from the deficiency of corticotropin-releasing hormone.…”
Section: Hiv Worldwide: Scope Of the Problemmentioning
confidence: 99%